Content Analysis of Geography Textbook Using Beck and McKeown Model on Natural Disaster Mitigation - Aliman, Muhammad; Supriyono, Supriyono; Halek, Dahri Hi; Lukman, Syahril; Sohnui, Suhailee; Marni, Silvia; Mike, Mike (JURNAL GEOGRAFI, 2025)
Quality textbooks are essential for developing critical thinking skills in geography education, especially for disaster mitigation in Indonesia's disaster-prone environment. To analyze the content quality of geography textbooks on natural disaster mitigation using the Beck and McKeown model and identify specific weaknesses. Qualitative content analysis with coding techniques was conducted on three geography textbooks for grade 11 students published by Erlangga, Grafindo Media Pratama, and Mediatama. A total of 226 paragraphs were analyzed using six adapted Beck and McKeown categories: problematic discussion, concept density, discourse clarity, main idea focus, example adequacy, and explanation structure. Analysis revealed quality issues across categories: 15.92% of paragraphs failed to present discussable problems, 6.19% contained excessive concepts, 4.86% lacked clear discourse, 3.53% presented multiple main ideas, 0.44% provided inadequate examples, and 1.33% showed illogical arrangements. Overall classification ranged from "good" to "very good" despite significant limitations. While textbooks met basic quality standards, substantial improvements are needed in problem-based content, concept organization, discourse clarity, and logical structuring to enhance critical thinking development for disaster education. This is the first application of the Beck and McKeown model to Indonesian geography textbooks focusing on disaster mitigation, providing a specialized assessment framework for disaster education materials. Findings offer actionable guidance for textbook authors, publishers, teachers, and policymakers to improve geography education quality and disaster preparedness literacy.